Pre-Bed Casein Protein Supplementation Does Not Enhance Acute Functional Recovery in Physically Active Males and Females When Exercise is Performed in the Morning - Eva Apweiler; David Wallace; Sarah Stansfield; Dean M. Allerton; Meghan A. Brown; Emma J. Stevenson; Tom Clifford (MDPI AG, 2018)
This study examined whether consuming casein protein (CP) pre-sleep could accelerate acute recovery following muscle-damaging exercise. Thirty-nine active males and females performed 100 drop jumps in the morning, consumed their habitual diet during the day, and then within 30 min pre-bed consumed either ~40 g of CP (n = 19) or ~40 g of a carbohydrate-only control (CON) (n = 20). Maximal isometric voluntary contractions (MIVC), countermovement jumps (CMJ), pressure-pain threshold (PPT), subjective muscle soreness and the brief assessment of mood adapted (BAM+) were measured pre, 24 and 48 h following the drop jumps. MIVC decreased in CP and CON post-exercise, peaking at 24 h post (CP: −8.5 ± 3.5 vs. CON: −13.0 ± 2.9%, respectively); however, no between-group differences were observed (p = 0.486; ηp2 =0.02). There were also no group differences in the recovery of CMJ height, PPT and BAM+ (p > 0.05). Subjective muscle soreness increased post-exercise, but no group differences were present at 24 h (CP: 92 ± 31 mm vs. CON: 90 ± 46 mm) or 48 h (CP: 90 ± 44 mm vs. CON: 80 ± 58 mm) (p > 0.05). These data suggest that pre-bed supplementation with ~40 g of CP is no more beneficial than CON for accelerating the recovery following muscle-damaging exercise.